Evaluation of 2-year outcomes following intravitreal bevacizumab (IVB) for aggressive posterior retinopathy of prematurity - Gunay,Murat (2015)
ABSTRACTPurpose:To evaluate 2-year outcomes following intravitreal bevacizumab (IVB) as monotherapy for aggressive posterior retinopathy of prematurity (APROP).Methods:Medical records of 40 infants were retrospectively reviewed. Group I included infants who had received IVB injections for APROP. Group II included infants who underwent laser treatment for APROP. Anatomic and refractive outcomes and the presence of anisometropia and strabismus were assessed at follow-up examinations.Results:Group I included 48 eyes of 25 infants (11 males) with a mean gestational age (GA) of 26.40 ± 1.82 weeks and a mean birth weight (BW) of 901.40 ± 304.60 g. Group II included 30 eyes of 15 infants (6 males) with a mean GA of 27.30 ± 1.82 weeks and a mean BW of 941.00 ± 282.48 g. GA, BW, and gender distributions were similar between groups (P=0.187, P=0.685, and P=1.000, respectively). Refractive errors were significantly less myopic in group I (0.42 ± 3.42 D) than in group II (-6.66 ± 4.96 D) at 2 years (P=0.001). Significantly higher rates of anisometropia and strabismus were observed in group II than in group I (P=0.009 and P=0.036, respectively).Conclusions:The study demonstrated that IVB monotherapy can be useful in the treatment of APROP. The decreased incidence of early unfavorable refractive and functional outcomes in the IVB group compared with the laser group showed a potential benefit for patients treated with IVB, and this needs to be better evaluated in future prospective studies.